2020
DOI: 10.3389/fpsyg.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Therapy for Adjustment Disorder in a Patient With Newly Diagnosed Pulmonary Arterial Hypertension: A Case Report

Abstract: Adjustment disorders (ADs) belong to the worldwide most diagnosed mental disorders and are particularly frequent in patients with an underlying physical illness. Pulmonary arterial hypertension (PAH) is a severe and disabling disease, which significantly impacts on quality of life and has high mortality rates. The authors here present the case of a young female who developed a severe adjustment disorder with both anxious and depressive symptoms after a diagnosis of PAH requiring intensive care treatment due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 45 publications
(47 reference statements)
6
15
0
Order By: Relevance
“…The results of the review mirror findings in mental health settings, which demonstrate that metacognitive beliefs are associated with anxiety and depression [29,[70][71][72][73][74][75][76][77] and that negative metacognitive beliefs of uncontrollability and danger show the strongest and most reliable relationships with these symptoms [29]. It seems therefore, that the relationships observed between anxiety, depression and metacognitions in non-clinical and mental health populations are similar to those found in patients with a range of physical health conditions.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The results of the review mirror findings in mental health settings, which demonstrate that metacognitive beliefs are associated with anxiety and depression [29,[70][71][72][73][74][75][76][77] and that negative metacognitive beliefs of uncontrollability and danger show the strongest and most reliable relationships with these symptoms [29]. It seems therefore, that the relationships observed between anxiety, depression and metacognitions in non-clinical and mental health populations are similar to those found in patients with a range of physical health conditions.…”
Section: Discussionsupporting
confidence: 60%
“…Fisher et al [ 68 ] evaluated metacognitive therapy for emotional distress in an open trial for adult cancer survivors. Winter et al [ 69 ] conducted a case study of MCT for adjustment disorder in a patient with pulmonary arterial hypertension. These initial studies suggest that MCT is an acceptable and feasible intervention that was associated with positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that this may have been the best time for therapeutic intervention, which may have prevented the development of manifest psychiatric disorders in some patients. Recently, successful psychological treatment of a patient with newly diagnosed PAH suffering from severe adjustment disorder using metacognitive treatment was described (22). Metacognitive treatment belongs to the wide spectrum of "third wave" cognitive behavioral therapies (23) and has the advantage of relatively short treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a higher prevalence of adjustment disorders among mental disorders in patients with PAH (13). Metacognitive treatment, a cognitive behavioral therapy, has been successfully applied to a patient with newly diagnosed PAH suffering from severe adjustment disorder (30,31). With only limited data on psychiatric treatment options in patients with PAH, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%